2021
DOI: 10.1111/jch.14159
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk assessment in children and adolescents with congenital solitary kidneys

Abstract: It is well known that patients with solitary kidneys (SKs) are at risk of hypertension (HT), proteinuria, and glomerulosclerosis due to their low number of nephrons. 1-4 They tend to have higher levels of HT-associated end-organ damage markers, such as left ventricular mass index (LVMI) and microalbuminuria. 5 Congenital SKs (CSKs) or acquired SKs (ASKs) have different effects on glomerular filtration rate (GFR) and blood pressure (BP).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 43 publications
(139 reference statements)
0
21
0
Order By: Relevance
“…Ten studies evaluated BP by ABPM in a total number of 379 children with CSK [ 28 , 32 , 37 , 70 – 75 , 85 ] (Table 7 ). Five studies reported data on kidney length for a total of 136 patients and about 86% presented compensatory enlargement [ 28 , 32 , 70 , 72 , 85 ].…”
Section: Should Ambulatory Blood Pressure Monitoring Be Performed In ...mentioning
confidence: 99%
See 4 more Smart Citations
“…Ten studies evaluated BP by ABPM in a total number of 379 children with CSK [ 28 , 32 , 37 , 70 – 75 , 85 ] (Table 7 ). Five studies reported data on kidney length for a total of 136 patients and about 86% presented compensatory enlargement [ 28 , 32 , 70 , 72 , 85 ].…”
Section: Should Ambulatory Blood Pressure Monitoring Be Performed In ...mentioning
confidence: 99%
“…Five studies reported data on kidney length for a total of 136 patients and about 86% presented compensatory enlargement [ 28 , 32 , 70 , 72 , 85 ]. Six studies reported data on ipsilateral CAKUT, which were present in a minority of patients [ 28 , 37 , 70 , 71 , 75 , 85 ], while in the study by Lubrano et al, 24 out of 38 had kidney scars [ 74 ]. Most of the children in these 10 studies had a GFR > 60 ml/min/1.73 m 2 , while approximately 22% of them had elevated office BP readings before ABPM.…”
Section: Should Ambulatory Blood Pressure Monitoring Be Performed In ...mentioning
confidence: 99%
See 3 more Smart Citations